Future Riverine Inorganic Nitrogen Load to the Baltic Sea From Sweden: An Ensemble Approach to Assessing Climate Change Effects. Issue 11 (23rd November 2017) - Teutschbein, C.; Sponseller, R. A.; Grabs, T.; Blackburn, M.; Boyer, E. W.; Hytteborn, J. K.; Bishop, K.
Abstract: The dramatic increase of bioreactive nitrogen entering the Earth's ecosystems continues to attract growing attention. Increasingly large quantities of inorganic nitrogen are flushed from land to water, accelerating freshwater, and marine eutrophication. Multiple, interacting, and potentially countervailing drivers control the future hydrologic export of inorganic nitrogen. In this paper, we attempt to resolve these land‐water interactions across boreal/hemiboreal Sweden in the face of a changing climate with help of a versatile modeling framework to maximize the information value of existing measurement time series. We combined 6, 962 spatially distributed water chemistry observations spread over 31 years with daily streamflow and air temperature records. An ensemble of climate model projections, hydrological simulations, and several parameter parsimonious regression models was employed to project future riverine inorganic nitrogen dynamics across Sweden. The median predicted increase in total inorganic nitrogen export from Sweden (2061–2090) due to climate change was 14% (interquartile range 0–29%), based on the ensemble of 7, 500 different predictions for each study site. The overall export as well as the seasonal pattern of inorganic nitrogen loads in a future climate are mostly influenced by longer growing seasons and more winter flow, which offset the expected decline in spring flood. The predicted increase in inorganic nitrogen loading due to climate change means that the political efforts for reducing anthropogenic nitrogen inputs need to be increased if ambitions for reducing the eutrophication of the Baltic Sea are to be achieved. Key Points: A systematic ensemble approach based on empirical inorganic nitrogen models provides robust estimates of future inorganic nitrogen dynamics The amount and seasonal variability of future inorganic nitrogen loads are controlled by shifts in growing season and streamflow patterns Annual inorganic nitrogen loads will rise as a result of rising winter streamflow, which will outweigh the decline in spring flood volume